Vowel perception in multilingual speakers: ERP evidence from Polish, English and Norwegian - Kędzierska, Hanna; Rataj, Karolina; Balas, Anna; Cal, Zuzanna; Castle, Chloe; Wrembel, Magdalena (Frontiers in Psychology, 2023)
Research on Mismatch Negativity (MMN) in monolingual and bilingual speakers has shown significant differences in L1 versus L2 phonemic perception. In this study, we examined whether the MMN response is sensitive to the differences between L1, L2 and L3/Ln. We compared bioelectrical brain activity in response to changes in pairs of vowels produced in three different languages. Specifically, multilingual participants listened to selected vowel contrasts in their L1 Polish, L2 English and L3/Ln Norwegian presented within the passive-oddball paradigm. Results revealed that the MMN was modulated by language: we observed significant differences between L2 English and L3/Ln Norwegian as well as between L1 Polish and L3/Ln Norwegian. For L3/Ln Norwegian, the MMN response had a lower amplitude when compared with L2 English and L1 Polish. Such findings suggest that foreign language status (i.e., L2 vs. L3/Ln) modulates early auditory processing.